2011
DOI: 10.1177/0264550511402271
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on depression, gender and crime: Depression sometimes masked, missed and misunderstood?

Abstract: This article offers both a literature review, and perspectives on the definition and nature of depressive illness, its various modes of presentation, and its significance in male, female and adolescent populations. It provides a brief review of some of the ideas about the aetiology of depression, outlines how to recognize it and discusses its relevance to forensic populations. Finally it suggests how early detection of depression and, consequently, more adequate access to treatment intervention, can be facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…According to Daigle and colleagues (2007) depression is correlated with a variety of negative outcomes, including delinquent and criminal behavior. Affective disorders are more prevalent among females than males (Hodgkinson and Prins, 2011). Furthermore, depression symptoms account for a significant amount of affective disorders experienced by females (Hodgkinson and Prins, 2011).…”
Section: Depression and Delinquencymentioning
confidence: 99%
See 4 more Smart Citations
“…According to Daigle and colleagues (2007) depression is correlated with a variety of negative outcomes, including delinquent and criminal behavior. Affective disorders are more prevalent among females than males (Hodgkinson and Prins, 2011). Furthermore, depression symptoms account for a significant amount of affective disorders experienced by females (Hodgkinson and Prins, 2011).…”
Section: Depression and Delinquencymentioning
confidence: 99%
“…Affective disorders are more prevalent among females than males (Hodgkinson and Prins, 2011). Furthermore, depression symptoms account for a significant amount of affective disorders experienced by females (Hodgkinson and Prins, 2011). For example, empirical studies have shown that females are twice as likely as males to experience symptoms of depression (e.g., Nolen-Hoeksema, 2001).…”
Section: Depression and Delinquencymentioning
confidence: 99%
See 3 more Smart Citations